Clonal hematopoiesis as a pitfall in germline variant interpretation in the context of Mendelian disorders. Issue 14 (18th February 2022) - Brunet, Theresa; Berutti, Riccardo; Dill, Veronika; Hecker, Judith S; Choukair, Daniela; Andres, Stephanie; Deschauer, Marcus; Diehl-Schmid, Janine; Krenn, Martin; Eckstein, Gertrud; Graf, Elisabeth; Gasser, Thomas; et al.
Abstract: Clonal hematopoiesis because of somatic mutations in hematopoietic stem/progenitor cells is an age-related phenomenon and commonly observed when sequencing blood DNA in elderly individuals. Several genes that are implicated in clonal hematopoiesis are also associated with Mendelian disorders when mutated in the germline, potentially leading to variant misinterpretation. We performed a literature search to identify genes associated with age-related clonal hematopoiesis followed by an OMIM query to identify the subset of genes in which germline variants are associated with Mendelian disorders. We retrospectively screened for diagnostic cases in which the presence of age-related clonal hematopoiesis confounded exome sequencing data interpretation. We found 58 genes in which somatic mutations are implicated in clonal hematopoiesis, while germline variants in the same genes are associated with Mendelian (mostly neurodevelopmental) disorders. Using five selected cases of individuals with suspected monogenic disorders, we illustrate how clonal hematopoiesis in either variant databases or exome sequencing datasets poses a pitfall, potentially leading to variant misclassification and erroneous conclusions regarding gene–disease associations.